Penguatan dan Tantangan Soft Diplomacy Australia di Kawasan Indo-Pasifik - Damayanti, Rizki - (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2024)
This research aims to investigate the strengthening and challenges faced by Australia's soft diplomacy in the Indo-Pacific region. The main focus of the research is on how Australia strengthens its presence in the Indo-Pacific region through various forms of public diplomacy, including cultural diplomacy, educational scholarships (New Colombo Plan and Australia Awards), and media diplomacy. The theory used is soft diplomacy which suggests that a country's influence in international relations is not only determined by military or economic strength, but also by its ability to influence and win the hearts and minds of people in other countries. The research method is a qualitative approach with data analysis from various sources of academic literature and official government documents. The research findings show that Australia has actively used soft diplomacy, but the research also identified that the soft diplomacy implemented by Australia in the Indo-Pacific region still has many weaknesses as a result of diplomatic tensions, perceptions of the Hyper-Pacific, limited resources, the complexity of regional dynamics, and Australia's inconsistency in determining priorities .